2019
DOI: 10.1016/j.cep.2019.107593
|View full text |Cite
|
Sign up to set email alerts
|

The influence of low-frequency magnetic field regions on the Saccharomyces cerevisiae respiration and growth

Abstract: The influence of four low-frequency magnetic field (MF) 1 ranges 10 -300 Hz, 10 -100 Hz, 10 -50 Hz and 50 -100 Hz in scanning regime (all frequencies from selected range were scanned during 100s repetitively during 24h) on baker's yeast cells Saccharomyces cerevisiae was examined by continuous measurements of cumulative O2 consumption and cumulative CO2 production over 24 h with Micro-Oxymax® respirometer. Besides respiration activity, measurements of cell growth and glucose uptake were performed as well. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Furthermore, the SMF increased the capability of the Defluviim bacteria to detoxify intermediates in azo dye degradation [62]. Enhanced cell anaerobic metabolism of yeast have been observed under low frequency magnetic fields [63]. Increasing the quantity and activity of methanogens is also an effective method to increase gas production [59].…”
Section: Vs In Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the SMF increased the capability of the Defluviim bacteria to detoxify intermediates in azo dye degradation [62]. Enhanced cell anaerobic metabolism of yeast have been observed under low frequency magnetic fields [63]. Increasing the quantity and activity of methanogens is also an effective method to increase gas production [59].…”
Section: Vs In Bmentioning
confidence: 99%
“…Furthermore, the SMF increased the capability of the Defluviimonas genus bacteria to detoxify intermediates in azo dye degradation [62]. Enhanced cell growth and anaerobic metabolism of yeast have been observed under low frequency (10-50 Hz) magnetic fields [63].…”
Section: Vs In Bmentioning
confidence: 99%
“…Bubanja et al [ 58 ] investigated the influence of low-frequency magnetic field regions on the respiration and growth of Saccharomyces cerevisiae. The study found statistically significant differences in cumulative oxygen consumption, cumulative carbon dioxide production, and S. cerevisiae cell number, which was attributed to the MF-induced stimulation of microbial growth and activity.…”
Section: Resultsmentioning
confidence: 99%
“…The observed differences in microbial population dynamics suggest that magnetic fields can potentially be used as a tool to manipulate the fermentation process and improve the quality of cocoa products. Moreover, it is noteworthy that the optimal intensity, duration, and other parameters of the magnetic field may vary depending on the specific fermentation process and the microbe being used [ 58 , 59 , 60 , 67 ].…”
Section: Resultsmentioning
confidence: 99%